Sodium intake and the risk of heart failure and hypertension: epidemiological and Mendelian randomization analysis - Yuan, Miao; Yan, Dingyi; Wang, Yu; Qi, Mengyao; Li, Kexin; Lv, Zhi; Gao, Dengfeng; Ning, Ning (Frontiers in Nutrition, 2024)
Background：This study aimed to analysis the relationship between sodium intake and the risk of heart failure and hypertension through epidemiological studies and Mendelian randomization analysis.Methods and result：We initially conducted an analysis using data from the National Health and Nutrition Examination Survey (NHANES) database to examine the relationship between sodium intake and heart failure, hypertension, systolic blood pressure, and diastolic blood pressure. After adjusting for confounding factors, we found a non-linear association between sodium intake and heart failure (p nonlinear = 0.0448). Subsequently, we utilized Mendelian randomization (MR) analysis by utilizing urinary sodium as a proxy for sodium intake to investigate the relationships between sodium and heart failure, hypertension, systolic blood pressure, and diastolic blood pressure. The results indicated that with increasing urinary sodium, there is an increase in systolic and diastolic blood pressure, as well as an elevated risk of heart failure and hypertension.The evidence provided by this study suggests that higher sodium intake is associated with an increased risk of heart failure and hypertension. However, excessively low sodium intake may not necessarily be beneficial, as there may be maximum benefits at a sodium intake level of around 3000 mg/d.